A new ricinuleid of the genus Ricinoides Ewing (Arachnida, Ricinulei) from Ghana - Naskrecki, Piotr (Zootaxa, 2008)
A new species of ricinuleid, Ricinoides atewa n. sp., is described from the Eastern Region of Ghana. This species is the largest known extant ricinuleid. It is associated with undisturbed, closed canopy, mid-elevation evergreen forests. Comparative illustrations are provided for the related species R. afzelii (Thorell, 1892).